EFL Students’ Perception on Technology: YouTube Application as Media in English Learning - harahap, addinul kamil; Farida Repeliwaty Kembaren (Institut Agama Islam Negeri Palopo, 2024)
In the current era, the challenges in the world of education are getting higher in meeting the needs of future generations in terms of learning, especially English, where English is used in technology languages ​​such as YouTube, etc., is very large. This is due to the rapid development of technology. In the world of education, their life experiences are also very different, especially the experience in using technology for children who come from underprivileged families, which is certainly different from children from upper-middle families in this regard. The Internet itself opens up many possibilities for integrating technology in classroom learning. Youtube is one of the learning media that can be integrated in learning subjects that are considered difficult by students. The purpose of this research is to see to what extent Youtube can be used as a medium of learning in school subjects, especially English. The results of the study show that videos on Youtube can be used as a learning medium.